IN THE NOVEL OF THE SKY IS EMPTY OVER OURSHALEEM BY SALEEM BARAKAT - IBRAHEEM, SAHL BAHAA AL-DEEN; MOHAMMED HASAN, DR. LATEEF (Journal of Duhok University, 2019)
The title remains the identity of the text and its main tool, as it regards one of the keys of the naara live text as a cognitive, expressive and Semantic top the text with a known delivery device. The aims of the novelist ( Saleem Barakat ) emerged through his internal and external titles, Characterized by its poetry Sometimes and philosophy at other time and third their Connection with each other . Thus the novelist achieved all that he hoped through his various titles to embody the texts and their consistency with the title evoking an amazing ability in expressing the content of the text .